PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KOMITMEN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Atmaja, I Komang Adi Wira; Adnyani, I Gusti Ayu Dewi (E-Jurnal Manajemen; Vol 5 No 11 (2016), 2016)
Organizational citizenship behavior is a voluntary behavior of a worker to want to do a task or work outside the responsibility or obligations for the sake of progress or profit organization. Successful organizations need employees who will do more than their formal duties and willing to deliver performance that exceeds expectations. The purpose of this study was to determine the direct effect of transformational leadership and organizational commitment on organizational citizenship behavior. This research was conducted at The Sand Beach Restaurant Bar & Grill Seminyak. The number of samples who were taken as many as 40 employees by using census method. Data collected through questionnaires using Likert scale. The analysis technique used is linear regression analysis of multiple. Based on analysis results found that transformational leadership style and Organizational commitment positive significant impact on organizational citizenship behavior.
Keywords: transformational leadership, organizational commitment, organizational citizenship behavior